Enhancing clinically-relevant shoulder function assessment using only essential movements. (18th February 2015) - Pichonnaz, C; Lécureux, E; Bassin, J-P; Duc, C; Farron, A; Aminian, K; Jolles, B M; Gleeson, N
Abstract: Kinematic functional evaluation with body-worn sensors provides discriminative and responsive scores after shoulder surgery, but the optimal movements' combination has not yet been scientifically investigated. The aim of this study was the development of a simplified shoulder function kinematic score including only essential movements. The P Score, a seven-movement kinematic score developed on 31 healthy participants and 35 patients before surgery and at 3, 6 and 12 months after shoulder surgery, served as a reference. Principal component analysis and multiple regression were used to create simplified scoring models. The candidate models were compared to the reference score. ROC curve for shoulder pathology detection and correlations with clinical questionnaires were calculated. The B–B Score (hand to the Back and hand upwards as to change a Bulb) showed no difference to the P Score in time*score interaction ( P > .05) and its relation with the reference score was highly linear ( R 2 > .97). Absolute value of correlations with clinical questionnaires ranged from 0.51 to 0.77. Sensitivity was 97% and specificity 94%. The B–B and reference scores are equivalent for the measurement of group responses. The validated simplified scoring model presents practical advantages that facilitate the objective evaluation of shoulder function in clinical practice.